Bio and non‐bio materials‐based quasi‐solid state electrolytes in DSSC: A review. (14th December 2021) - Mahalingam, Savisha; Nugroho, Agung; Floresyona, Dita; Lau, Kam Sheng; Manap, Abreeza; Chia, Chin Hua; Afandi, Nurfanizan
Summary: Dye‐sensitized solar cells (DSSCs) are more attractive than silicon solar cells due to their low dependency on light intensity so that they can perform both indoor and outdoor with low‐level lightings. DSSC's global revenue exceeded 16 million USD in 2014 for emerging portable charging, solar bags, and wireless keyboards. However, on‐grid DSSC modules are still under R&D for massive commercialization to improve their long‐term stability and safety issues due to the liquid electrolyte leakage. Therefore, quasi‐solid‐state electrolytes (QSE) have been proposed as a novel alternative to overcome the limitations stated above since 2001. Here, we deliver a short outline of the QSE properties, which are linked with the performance of DSSC in terms of different types of QSE structures: gel, hydrogel, and aerogel. Furthermore, these QSE structures are classified under bio and non‐bio materials. Finally, the impact, outlook, and future prospects of QSE‐DSSC are included as a conclusion in this review. Abstract : Overview of Bio and Non‐bio Electrolyte Type in DSSC